A comparative study of prevalence of overweight and obesity among urban, and rural population of South India - Babu Rao, B.; Junapudi, Syam Sundar (International Journal Of Community Medicine And Public Health, 2019)
Background: Obesity is a medical condition in which excess body fat has accumulated to the extent that it may have a negative effect on health.1 People are generally considered obese when their body mass index (BMI), a measurement obtained by dividing a person's weight by the square of the person's height, is over 30 kg/m2, with the range 25–30 kg/m2 defined as overweight.Aims and objectives were to estimate the prevalence of overweight and obesity among the study population and to compare the study results between urban and rural area population. Methods: A community based cross-sectional study from April 2008 to May 2009 (1 year) conducted at urban health centre, Harazpenta and rural health centre, Patancheruvu. Total of 1409 persons in the age group of above 15 years were involved in this study. Data collection by using pre-designed, pretested questionnaire. Data analysis by using MS office 2016. Epi info2016, rates, ratios, proportions and Chi-square tests were used. Results: Among urban population prevalence of obesity was 12.7% compared to 5.4% in rural area. The prevalence of pre obesity was more among males (26.2%) in urban area than rural area (16.72%). In the study population 42.9% of the individual who had BMI>25 were from upper middle class in urban area, when compared to 43.3% with BMI>25 belongs to upper class in rural area. Conclusions: All over weight and obese subjects should be educated to know about the occurrence of various health problems due to overweight.